Evolution Of Economics Macro - Monika Sutarsa; Andi Usmar (EKOBIMA, 2023)
Macroeconomics is a branch of economics that studies the overall economic system, including economic growth, unemployment, inflation and others. In the 21st century, macroeconomics continues to develop with the emergence of modern macroeconomic theory that emphasizes the role of monetary and fiscal policies in regulating the economy. In addition, technological developments and epidemics also affect macroeconomic developments in the world. This study aims to analyze economic development from the time of the Prophet and the Khulafa Al-Rasyidin (7th century) to the present. The method used in this study is a qualitative descriptive method by collecting secondary data from various related sources. Then the data is analyzed using a comparative method to find out what economic developments have occurred from the time of the Prophet and the Caliph until now. Thus, the evolution of the world's macro-economy has undergone many changes from the 7th century to the present, especially in the prevailing economic system, the factors influencing economic growth, and the ways in which people govern and manage resources.